2016
DOI: 10.1371/journal.pone.0166910
|View full text |Cite
|
Sign up to set email alerts
|

Non-Specific Root Transport of Nutrient Gives Access to an Early Nutritional Indicator: The Case of Sulfate and Molybdate

Abstract: Under sulfur (S) deficiency, crosstalk between nutrients induced accumulation of other nutrients, particularly molybdenum (Mo). This disturbed balanced between S and Mo could provide a way to detect S deficiency and therefore avoid losses in yield and seed quality in cultivated species. Under hydroponic conditions, S deprivation was applied to Brassica napus to determine the precise kinetics of S and Mo uptake and whether sulfate transporters were involved in Mo uptake. Leaf contents of S and Mo were also quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In this study, the composition of the nutrient solution was adapted so as to obtain plant mineral compositions that were as close as possible to those of plants grown under field conditions ( Supplementary Data SD1 ). To do so, the mineral compositions of B. napus leaves grown under hydroponic conditions ( Maillard et al, 2015 ) were compared to the leaf mineral compositions of plants grown under field conditions (derived from the data of Sarda et al (2013) and Maillard et al, 2016b , corresponding to 194 field plots randomly harvested in France). The nutrient solution contains: 1 mM KNO 3 , 1.25 mM Ca(NO 3 ) 2, 0.2 mM KH 2 PO 4 , 0.4 mM MgSO 4 , 0.5 μM NaFe-EDTA, 50 μM NaFe-EDDHA, 10 μM H 3 BO 3 , 3 μM MnSO 4 , 3 μM ZnSO 4 , 0.7 μM CuSO 4 , 0.008 μM (NH 4 ) 6 Mo 7 O 24 , 0.1 μM CoCl 2 , 0.15 μM NiCl 2 , 0.9 mM Si(OH) 4 , 0.5 mM CaCl 2 , 0.1 mM KCl, 0.01 μM Na 2 SeO 4 , 0.1 mM K 2 SO 4 , and 0.2 mM Na 2 SiO 3 buffered to pH 6.8 with 0.36 mM CaCO 3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the composition of the nutrient solution was adapted so as to obtain plant mineral compositions that were as close as possible to those of plants grown under field conditions ( Supplementary Data SD1 ). To do so, the mineral compositions of B. napus leaves grown under hydroponic conditions ( Maillard et al, 2015 ) were compared to the leaf mineral compositions of plants grown under field conditions (derived from the data of Sarda et al (2013) and Maillard et al, 2016b , corresponding to 194 field plots randomly harvested in France). The nutrient solution contains: 1 mM KNO 3 , 1.25 mM Ca(NO 3 ) 2, 0.2 mM KH 2 PO 4 , 0.4 mM MgSO 4 , 0.5 μM NaFe-EDTA, 50 μM NaFe-EDDHA, 10 μM H 3 BO 3 , 3 μM MnSO 4 , 3 μM ZnSO 4 , 0.7 μM CuSO 4 , 0.008 μM (NH 4 ) 6 Mo 7 O 24 , 0.1 μM CoCl 2 , 0.15 μM NiCl 2 , 0.9 mM Si(OH) 4 , 0.5 mM CaCl 2 , 0.1 mM KCl, 0.01 μM Na 2 SeO 4 , 0.1 mM K 2 SO 4 , and 0.2 mM Na 2 SiO 3 buffered to pH 6.8 with 0.36 mM CaCO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Arabidopsis Columbia wild type (Col) and sultr1.1 (SALK_093256) and sultr1.2 (sel1-8; Shibagaki et al, 2002 ) mutants previously grown under high or low S conditions by Maillard et al (2016b) were used for determination of their leaf V concentration. Briefly, Arabidopsis (Col or mutant lines) was grown for 17 days on agarose plates with a modified Long Ashton nutrient solution containing a high (0.75 mM) or low (0.075 mM) supply of sulfate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant analyses appear to be a better method for identifying S deficiency and evaluate soil fertility and crop management strategies [ 17 ]. Different indicators of S nutrition using plant analysis have been proposed, i.e., the N:S ratio [ 18 ], the SO 4 2− :total S ratio ([ 19 ], SO 4 2− [ 20 ]), total S (Pinkerton 1998 [ 21 ], the malate:SO 4 2− ratio [ 22 ], the molybdenum:S ratio [ 23 ],glutathione [ 24 ], amides [ 24 ], or expression of sulfur deficiency responsive genes[ 25 , 26 ], each presenting the advantages and drawbacks. Gene expression has potential as a sensitive indicator of S nutritional status because of its very early response of plant to S deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the reliability of the malate:SO 4 2− ratio indicate that it overestimated diagnosis of S deficiency and suggested that threshold values need to be reconsidered [ 33 , 34 ]). More recently, Maillard et al [ 23 ] have demonstrated that the [Mo]/[S] constitutes an accurate indicator to diagnose S deficiency. However, because the range of Mo leaf contents are usually low, measurements of this element need complex and senesitive laboratory methods (such as ICPMS-HR) which make difficult to use routinely this diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%